Lippia ganevii (Verbenaceae), a new combination for Lantana hatschbachii Moldenke, now validly published - Salimena, Fátima Regina G.; Múlgura, Maria Ema; Pastore, Jose Floriano Barêa (Phytotaxa, 2017)
A new combination for Lantana hatschbachii, earlier defectively published as Lippia ganevii, is provided. The species is currently known exclusively from the type locality in the municipality of Morro do Chapéu, Bahia, Brazil, in the rocky-field vegetation of the Chapada Diamantina. The species is characterized by oval-triangular to reniform leaves with a cordate to truncate base and lanceolate bracts covered by glandular trichomes.